Lead and Copper Heavy Metal Content in the Morosari Waters, Demak Region - Saraswati, Suprabadevi Ayumayasari; Toruan, Lumban Nauli Lumban; Susetya, Ipanna Enggar (Advances in Tropical Biodiversity and Environmental Sciences; Vol 7 No 1 (2023): ATBESDO - 10.24843/ATBES.2023.v07.i01.p06, 2023)
The utilization of river bodies as waste disposal has an impact on the entry of heavy metals into the sea. The Morosari estuary area is an estuary area, which consists of mangrove areas, tourist areas, and several industrial activities, both large-scale and household. This condition causes the entry of waste containing heavy metals lead (Pb) and copper (Cu) into the estuary area. This study aims to determine the content of heavy metals Pb and Cu in the estuary of the Morosari River. This research was conducted in April - June 2009 and took place in the Morosari River estuary, Demak Region. The research method used was a descriptive exploratory method, while the sampling was purposive. random sampling, to 3 stations. Water samples are taken every 2 weeks, and followed by an analysis carried out at the Growth Center Laboratory, Kopertis Region IV, Semarang. The data obtained were analyzed descriptively. Analysis results for Pb content in water: 0.039 - 0.089 and Cu content in water 0.024 - 0.055 mg/l. The value of heavy metal content in the water has exceeded the threshold.